(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
Serhiy Yefremov is one of the greatest Ukrainian literary scholars of the first decades of the twentieth century. His scholarly work began when Ivan Franko was still in power, and Mikhailo Hrushevsky became mature, and Mykola Yevshan was rapidly expanding. The article deals with the memoirs of S. Yefremov "Pro dni mynuli", which appeared only in 2011. The author on the foreground makes the problem far from paramount, but clearly identifies the potential of the author of memoirs as a wonderful physiognomist, a person who can recognize the mental state of the hero of memoirs, his inner world in appearance and facial expressions. These are the features of portraiture in the memoirs of S. Yefremov. Most often, this author uses an expanded portrait of a real hero, which consists of several paragraphs and can be static, that is, concentrated in one place of the work or dynamic, scattered by separate splashes in different places. Portrait of S. Yefremov is created on the basis of personal impressions in communication of the author with real heroes, fellow villagers, family members, friends, acquaintances, but always complemented by certain weighty details that make the personality figure more voluminous, psychologically motivated. The creative imagination, deliberation and fiction the memoirist tries to minimize, as if striving, so that the reader has the opportunity to fully comprehend the figure of a real person, a hero of memoirs, among which there are quite well-known personalities in the history of Ukrainian culture (I. Nechui-Levytsky, O. Konysky, V. Antonovich).